2014
DOI: 10.1128/jb.01475-14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iron and Aeration on Staphylococcus aureus Growth, Metabolism, and Transcription

Abstract: Staphylococcus aureus is a prominent nosocomial pathogen and a major cause of biomaterial-associated infections. The success of S. aureus as a pathogen is due in part to its ability to adapt to stressful environments. As an example, the transition from residing in the nares to residing in the blood or deeper tissues is accompanied by changes in the availability of nutrients and elements such as oxygen and iron. As such, nutrients, oxygen, and iron are important determinants of virulence factor synthesis in S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 63 publications
5
62
0
Order By: Relevance
“…27–32 Consistent with these studies, we detected higher levels of intracellular lactate in all bacteria by 2D 1 H- 13 C HSQC NMR during anaerobiosis (Fig 3A and B). However, when compared to the wild-type strain, we observed decreased concentrations of intracellular lactate in the pta and ackA mutants under fermentative growth (Fig 3A).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…27–32 Consistent with these studies, we detected higher levels of intracellular lactate in all bacteria by 2D 1 H- 13 C HSQC NMR during anaerobiosis (Fig 3A and B). However, when compared to the wild-type strain, we observed decreased concentrations of intracellular lactate in the pta and ackA mutants under fermentative growth (Fig 3A).…”
Section: Resultssupporting
confidence: 85%
“…10, 30, 32, 38, 39 We have previously shown that under these conditions the Pta-AckA pathway plays an indispensable role in maintenance of S. aureus fitness, as its inactivation results in growth defects and cell death. Although the precise reasons for the observed defects in growth and viability of pta and ackA mutants are not clearly understood, a role for ATP production (a byproduct of the Pta-AckA pathway) was ruled out earlier.…”
Section: Discussionmentioning
confidence: 99%
“…To modulate the concentration of dioxygen in the culture medium, we varied the ratio of liquid medium volume to culture vessel to gaseous headspace (HV ratio). The higher the HV ratio, the higher the concentration of dissolved dioxygen (34). The sodA::Tn mutant had decreased AcnA activity when cultured at an HV ratio of 20, but the AcnA activity was comparable to that of the WT when cultured at an HV ratio of 2.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and small putative FeoC-like proteins are encoded within the feo gene cluster in these organisms (Cartron et al, 2006). The Staphylococcus aureus feoAB(C) locus is upregulated during iron starvation in a Furdependent manner (Lin et al, 2012;Ledala et al, 2014).…”
Section: Ferrous Iron Uptakementioning
confidence: 99%